O cinema na literatura de Caio Fernando Abreu: procedimentos cinematográficos em Morangos mofados - Guanabara, Luisa Vianna Santos (2021)
This project’s purpose is to investigate and discuss which cinematographic procedures were used to compose the writing of Morangos mofados (1982) by Caio Fernando Abreu. In which way the experience of cinema impacts the poetics of the cinephile writer? Through the analysis of presence of movies and soundtracks referenced by Abreu in his tales and mail, our intent is to understand to which narrative tradition, classic or contemporary, he affiliates himself. To that end, the present reading evokes the following pieces on screenwriting in order to comprehend the way of narrating celebrated by the author: Literature through Cinema: Realism, magic and the art of adaptation, by Robert Stam, and Dominant Narrative Cultures: the case of cinema, by Joao Maria Mendes. As a result, one hopes to contribute to the comparative studies that dedicate themselves to relationships between literature and cinema